การพัฒนาครูในการจัดการเรียนรู้โดยใช้ Google Apps for Education วิทยาลัยเทคนิคเขาวง สังกัดสำนักงานคณะกรรมการการอาชีวศึกษา - จิตจักร, สมปรารถนา; มารี เคน, ปาริชา; ภูดี, ธีระ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 3 No 3 (2566): กันยายน-ธันวาคม 2566, 2023)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาสภาพ ปัญหา แนวทางการพัฒนา และผลการพัฒนาครูในการจัดการเรียนรู้ โดยใช้ Google Apps for Education วิทยาลัยเทคนิคเขาวง  สังกัดสำนักงานคณะกรรมการการอาชีวศึกษา โดยใช้รูปแบบการวิจัยเชิงปฏิบัติการ กลุ่มเป้าหมาย ได้แก่ กลุ่มผู้ร่วมวิจัย จำนวน 8 คน ได้มาโดยวิธีเลือกแบบเจาะจง เครื่องมือที่ใช้ ได้แก่ แบบสัมภาษณ์ แบบประเมิน แบบบันทึกสรุปการประชุม แบบทดสอบ แบบบันทึกชุมชนแห่งการเรียนรู้ทางวิชาชีพ แบบสะท้อนผลการปฏิบัติงาน วิเคราะห์ข้อมูลเชิงปริมาณใช้ค่าสถิติ ค่าเฉลี่ย ค่าส่วนเบี่ยงเบนมาตรฐาน และค่าร้อยละความก้าวหน้า ผลการวิจัยพบว่า 1. สภาพและปัญหาของครูในการจัดการเรียนรู้ โดยใช้ Google Apps for Education พบว่า วิทยาลัยยังไม่เคยมีการจัดประชุมเชิงปฏิบัติการ ผู้บริหารมีการสนับสนุนด้านสัญญาณอินเตอร์เน็ตแต่ยังไม่เสถียร วัสดุ อุปกรณ์ บางส่วนใช้ไม่ได้ ครูผู้สอน มีความรู้ ทักษะพื้นฐานในการใช้ Google Apps for Education แหล่งข้อมูลในการศึกษาภายในวิทยาลัยยังมีบริการน้อย ตัวแทนครูที่เคยอบรมออนไลน์ยังไม่มีโอกาสถ่ายทอดความรู้ และผู้ร่วมวิจัยมีความต้องการให้จัดประชุมเชิงปฏิบัติการ 2. แนวทางการพัฒนาครูในการจัดการเรียนรู้ โดยใช้ Google Apps for Education มี 2 แนวทาง คือ การประชุมเชิงปฏิบัติการ และการสร้างชุมชนแห่งการเรียนรู้ทางวิชาชีพ 3. ผลการพัฒนาครูในการจัดการเรียนรู้ โดยใช้ Google Apps for Education วิทยาลัยเทคนิคเขาวง สังกัดสำนักงานคณะกรรมการการอาชีวศึกษา 1) ผู้ร่วมวิจัยมีความรู้ ความเข้าใจในการจัดการเรียนรู้ โดยใช้ Google Apps for Education เพิ่มขึ้น 2) ผลจากการการพัฒนาครูด้วยกระบวนการชุมชนแห่งการเรียนรู้ทางวิชาชีพ ผู้ร่วมวิจัยสามารถนำไปใช้ในการจัดการเรียนรู้และสามารถหาแนวทางในการแก้ปัญหาได้เป็นอย่างดี The purpose of this research is to study the conditions, problems, development guidelines and teacher development results in learning management by using Google Apps for Education, Khao Wong Technical College Under the Office of the Vocational Education Commission using an action research model Target groups include A group of 8 participants was obtained by purposive selection. The tools used were interview forms, assessment forms, meeting summaries, tests, and professional learning community records. performance reflection form Quantitative data were analyzed using statistics, means, standard deviations and progress percentage. The research results were as follows: 1. The condition and problems of teachers in learning management using Google Apps for Education found that the college had never held a workshop. Administrators have Internet signal support but are not stable. Some materials and equipment are unusable. Teachers have knowledge and basic skills in using Google Apps for Education. There are few educational resources within the college. Teacher representatives who have trained online do not yet have the opportunity to pass on their knowledge. and the co-researchers wanted to organize a workshop. 2. Guidelines for developing teachers it was found that there were 2 approaches: workshops and building a professional learning community 3. The results of teacher development in learning management by using Google Apps for Education, Khao Wong Technical College. Under the Office of the Vocational Education Commission, it was found that 1) The research participants had knowledge Increased understanding of learning management using Google Apps for Education. 2) The results of teacher development through the professional learning community process, it was found that the research participants were able to use it in learning management and were able to find ways to solve problems very well.